Faktor-faktor yang Memengaruhi Nilai Perusahaan - Dinda Alifiah Anggreani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify factors that influence firm value. The sample in this study includes mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023 with certain criteria. The sample selection method in this study used purposive sampling with a sample of 99 companies. This study uses multiple regression analysis techniques. The results of the study show that managerial ownership, independent commissioners, and corporate social responsibility have no effect on firm value. Meanwhile, the audit committee has a positive effect on firm value and institutional ownership has a negative effect on firm value.